2000
DOI: 10.1111/j.1553-2712.2000.tb01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Sensitivity and Specificity of Pediatric Trauma Team Activation Criteria

Abstract: Abstract. Background: Care of the severely injured child requires the rapid assembly of personnel trained in pediatric trauma care. Trauma team activation criteria, which are highly sensitive and maximally specific for identifying the child who requires resuscitation, are necessary to provide rapid care to all who need it, while using resources efficiently. Objective: To determine the sensitivity and specificity of the standard trauma team activation (TTA) criteria for identifying patients who receive resuscit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…The study also found that injury mechanism was less accurate as a triage criterion, as were the Pediatric Trauma Score [36] and Revised Trauma Score systems of triage [37]. Studies in the United States and Denmark report similar findings [38,39]. These studies also found that the use of anatomic and physiologic criteria retains a high sensitivity for identifying children in need of resuscitative interventions and reduces overtriage.…”
Section: Overtriagesupporting
confidence: 61%
“…The study also found that injury mechanism was less accurate as a triage criterion, as were the Pediatric Trauma Score [36] and Revised Trauma Score systems of triage [37]. Studies in the United States and Denmark report similar findings [38,39]. These studies also found that the use of anatomic and physiologic criteria retains a high sensitivity for identifying children in need of resuscitative interventions and reduces overtriage.…”
Section: Overtriagesupporting
confidence: 61%
“…This study did not use the minimum criteria defined by the Committee on Trauma nor did it attempt to look at specific criteria for accurately triaging patients. Mechanism of injury has not been shown to be a good predictor of patients who need level I activation [5,6]. Dowd et al [5] pointed out that using anatomic and physiological criteria for trauma team activation reduced over triage yet maintained the sensitivity of the outcome of resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism of injury has not been shown to be a good predictor of patients who need level I activation [5,6]. Dowd et al [5] pointed out that using anatomic and physiological criteria for trauma team activation reduced over triage yet maintained the sensitivity of the outcome of resuscitation. This study points out that criteria for determining the level of activation must take into account over and under triage, both of which may result in a suboptimal patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have correlated physiologically focused trauma activation criteria with other outcomes such as the need for fluid resuscitation or any surgical intervention [14]. However, these end points do not necessarily predict outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Triage criteria based on Glasgow coma scale, hypotension, tachypnea, hypoventilation, or need for endotracheal intubation in the prehospital setting have been found to be safe while reducing overtriage in adult blunt trauma patients [12,13]. Furthermore, eliminating mechanism-based triage criteria for blunt trauma has been shown to be safe in children [14]. Intubation and respiratory derangement, including tachypnea, predicted outcome for pediatric blunt trauma patients [15] and battlefield trauma victims [16], but not the necessity for surgical trauma team activation (S-TTA) [17,18].…”
mentioning
confidence: 98%